Controls of microgrid - Tay, Cheryl Ruiqi (Nanyang Technological University, 2022)
The usage of renewable sources of energy is on the upward trend. However, this is heavily dependent on atmospheric conditions which causes unreliability of power generation, and it is still yet unable to meet the amount needed for full scale industrial usage. Battery storage system will help ease these issues and benefit the system by balancing frequency if there is a fluctuation in the load demand.